2021
DOI: 10.1016/j.jinsphys.2021.104262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, fungal infection and weight on intermoult duration and survival of starving earwig larvae

Abstract: Moulting is a cornerstone of arthropods development. It can be determined by numerous factors such as body mass, temperature, and immunity. However, the effects of these factors can be dependent on each other, so that it is often difficult to predict whether and how they shape moulting, and whether their effects are additive or interactive. In this study, we addressed these questions by testing the effects of body mass, ambient temperature, fungal infection and their interaction on intermoult duration and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Temperature is a critical abiotic factor and has a vast influence on various aspects of the performance of insects (Angilletta et al, 2004;Berger et al, 2012;Kingsolver and Huey, 2008). Temperature also plays a role in an insect's ability to fight off an infection (Coulm and Meunier, 2021;Linder et al, 2008;Thomas and Blanford, 2003) and impacts the interaction between the host and pathogen by influencing the growth and virulence of the pathogen (Arthurs and Thomas, 2001;Catalán et al, 2012). Studies have shown that warmer temperatures are likely to increase insect's immunity response by causing an increase in immune parameters such as PO and lysozyme-like enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is a critical abiotic factor and has a vast influence on various aspects of the performance of insects (Angilletta et al, 2004;Berger et al, 2012;Kingsolver and Huey, 2008). Temperature also plays a role in an insect's ability to fight off an infection (Coulm and Meunier, 2021;Linder et al, 2008;Thomas and Blanford, 2003) and impacts the interaction between the host and pathogen by influencing the growth and virulence of the pathogen (Arthurs and Thomas, 2001;Catalán et al, 2012). Studies have shown that warmer temperatures are likely to increase insect's immunity response by causing an increase in immune parameters such as PO and lysozyme-like enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic examination is often used to clarify the characteristics and drug resistance of secondary fungal infection in immune-related lung diseases. However, the error of this method is large, and there may be false positives, which requires more reliable diagnostic methods [ 5 , 6 ]. Studies have shown that the ideal marker detection can judge the ability of fungal infection and distinguish the relationship between fungal infection and other infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although earwigs can be beneficial in certain systems since they feed on other arthropods, they are a problem in soft-fruited systems like peach since they burrow into the soft crop (Orpet et al 2019). While some work has assessed earwig management, a more thorough investigation which accounts for earwig development rate (Coulm and Meunier 2021), localized migration from the orchard floor into the canopy, and the orchard-wide dispersal rate of the entire population is necessary. In our system, we noticed that earwigs did not damage fruits until they began to ripen (D. Alston, personal observation).…”
Section: Discussionmentioning
confidence: 99%